Dipirona versus paracetamol no controle da dor pós-operatória - Queiroz, Thallita Pereira; Santos, Pâmela Letícia Dos; Esteves, Jônatas Caldeira [UNESP]; Stellin, Gustavo Marco; Shimuzi, Aline Sayuri [UNESP]; Betoni Junior, Walter; Vieira, Eduardo Hochuli [UNESP] (Universidade Estadual Paulista Júlio de Mesquita Filho, 2013)
INTRODUCTION: The pain is defined as an unpleasant experience, and control of postoperative pain a great challenge in healthcare. OBJECTIVE: To compare the efficacy of Dipyrone and acetaminophen in postoperative pain after third molar surgery. MATERIAL AND METHOD: Thirty patients of the Discipline of Surgery of School of Dentistry of Araçatuba - UNESP, that needed to extract their third included molars, were selected. Among these, 15 received Dipyrone (group I) and the other received acetaminophen (group II) in the postoperative. All patients were treated pre-operatively with dexamethasone 4 mg and amoxycillin 1 g, one hour before surgery. Pain intensity was evaluated by a visual analogue scale by forty eight hours postoperative period and in intervals of six hours. The exclusion criteria were: presence of systemic disorders, drugs hypersensitivity, pregnant, lactic and local contraindications. The scores obtained were submitted to the Mann-Whitney test (p < 0,05) for comparison of the pain intensity in the 6 hours intervals, in the initial 24 hours, in the last 24 hours and in the total period of 48 hours. RESULT: There was no statistical difference among the analgesics in the 6 hours intervals, however, in the last 24 hours and in the total period of 48 hours, the group I presented smaller medium values, significant statistically, when compared to group II. CONCLUSION: The analgesic efficacy of dipyrone was superior to paracetamol.

INTRODUÇÃO: A dor é definida como uma experiência desagradável, sendo o controle da dor pós-operatória um grande desafio na área da saúde. OBJETIVO: Comparar a eficácia da dipirona e do paracetamol no controle da dor pós-operatória após exodontia de terceiros molares inclusos. MATERIAL E MÉTODO: Foram selecionados 30 pacientes da Disciplina de Cirurgia da Faculdade de Odontologia de Araçatuba - UNESP, que necessitavam extrair os terceiros molares inclusos. Desses, 15 receberam dipirona (Grupo I) e outros 15 receberam paracetamol (Grupo II) no pós-operatório. Todos os pacientes foram tratados, no pré-operatório, uma hora antes do procedimento cirúrgico, com dexametasona 4 mg e amoxicilina 1 grama. A intensidade da dor foi avaliada pelos pacientes por meio de escala visual analógica, em um período pós-operatório de 48 horas, em intervalos de 6 horas. Os critérios de exclusão foram: presença de desordens sistêmicas, hipersensibilidade medicamentosa, gestação, lactação e contraindicações locais. Os escores obtidos foram submetidos ao teste de Mann-Whitney (α = 0,05) para comparação das intensidades de dor em intervalos de 6 horas, nas 24 horas iniciais, nas 24 horas finais e no período total de 48 horas. RESULTADO: Não houve diferença estatística entre os analgésicos estudados nos intervalos de 6 horas; entretanto, nas 24 horas finais e nas 48 horas totais de observação, o Grupo I apresentou valores médios menores, estatisticamente significantes, quando comparado ao Grupo II. CONCLUSÃO: A eficácia analgésica da dipirona foi superior à do paracetamol.
Dipyrone versus acetaminophen in the control of postoperative pain
Keywords: Analgesia; molar, third; acetaminophen; dipyrone; Analgesia; terceiro molar; acetaminofen; dipirona